ANALYSIS OF MOBILE LEGENDS INSTAGRAM SOCIAL MEDIA CONTENT COPYWRITING AND SYMBOLIC MEANING - Zaqy Alpippo Virgiawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Instagram serves as a primary platform for Mobile Legends: Bang Bang (MLBB) to communicate with its vast Indonesian player base. This study aims to analyze the copywriting techniques and symbolic meanings embedded in the content of the official MLBB Instagram account, @realmobilelegendsid. Using a qualitative descriptive approach, data were collected through observation and documentation of posts from January to March 2025. The analysis employs the AIDA (Attention, Interest, Desire, Action) copywriting model and Roland Barthes' semiotic theory to deconstruct denotative, connotative, and mythological meanings. The findings reveal that the captions are effective in capturing Attention and building Interest through informative and direct messages. However, they are weak in cultivating Desire and prompting Action, as they lack emotional storytelling, persuasive language, and strong calls-to-action (CTA). Semiotic analysis shows that visual content constructs connotations of status, self-actualization, and community belonging, while perpetuating myths that dedicated gamers possess premium skins and actively participate in exclusive events. This study concludes that while @realmobilelegendsid's content is informationally effective, there is significant potential to enhance audience engagement by integrating more emotionally resonant copywriting and strategically leveraging symbolic meanings.